Towards the development of continuous, organocatalytic, and stereoselective reactions in deep eutectic solvents - Brenna, Davide; Massolo, Elisabetta; Puglisi, Alessandra; Rossi, Sergio; Celentano, Giuseppe; Benaglia, Maurizio; Capriati, Vito (Beilstein Journal of Organic Chemistry, 2016)
Different deep eutectic solvent (DES) mixtures were studied as reaction media for the continuous synthesis of enantiomerically enriched products by testing different experimental set-ups. L-Proline-catalysed cross-aldol reactions were efficiently performed in continuo, with high yield (99%), anti-stereoselectivity, and enantioselectivity (up to 97% ee). Moreover, using two different DES mixtures, the diastereoselectivity of the process could be tuned, thereby leading to the formation, under different experimental conditions, to both the syn- and the anti-isomer with very high enantioselectivity. The excess of cyclohexanone was recovered and reused, and the reaction could be run and the product isolated without the use of any organic solvent by a proper choice of DES components. The dramatic influence of the reaction media on the reaction rate and stereoselectivity of the process suggests that the intimate architecture of DESs deeply influences the reactivity of different species involved in the catalytic cycle.
Keywords: continuous process; DES; organocatalysis; proline; stereoselective aldol reaction

Modern Aldol Reactions - Mahrwald, R. (Wiley-VCH, 2004)

Asymmetric Organocatalysis - Berkessel, A.; Gröger, H. (Wiley-VCH, 2005)

(untitled) - List, B.; Lerner, R. A.; Barbas, C. F., III (J. Am. Chem. Soc., 2000)

(untitled) - Liu, X.; Lin, L.; Feng, X. (Chem. Commun., 2009)

(untitled) - Orlandi, M.; Benaglia, M.; Raimondi, L.; Celentano, G. (Eur. J. Org. Chem., 2013)

(untitled) - Guizzetti, S.; Benaglia, M.; Pignataro, L.; Puglisi, A. (Tetrahedron: Asymmetry, 2006)

(untitled) - Cho, E.; Kim, T. H. (Tetrahedron Lett., 2014)

(untitled) - Karmakar, A.; Maji, T.; Wittmann, S.; Reiser, O. (Chem. – Eur. J., 2011)

(untitled) - Opalka, S. M.; Steinbacher, J. L.; Lambiris, B. A.; McQuade, D. T. (J. Org. Chem., 2011)

(untitled) - El-Hamdouni, N.; Companyó, X.; Rios, R.; Moyano, A. (Chem. – Eur. J., 2010)

(untitled) - Reis, O.; Eymur, S.; Reis, B.; Demir, A. S. (Chem. Commun., 2009)

(untitled) - Mandal, T.; Zhao, C.-G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Clarke, M. L.; Fuentes, J. A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Rodriguez, B.; Bruckmann, A.; Bolm, C. (Chem. – Eur. J., 2007)
See for ball mill approach.

(untitled) - Clegg, W.; Harrington, R. W.; North, M.; Pizzato, F.; Villuendas, P. (Tetrahedron: Asymmetry, 2010)
See for the use of carbamates.

(untitled) - Mase, N.; Nakai, Y.; Ohara, N.; Yoda, H.; Takabe, K.; Tanaka, F.; Barbas, C. F., III (J. Am. Chem. Soc., 2006)
See for aldol reaction on water.

(untitled) - Hayashi, Y.; Sumiya, T.; Takahashi, J.; Gotoh, H.; Urushima, T.; Shoji, M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Guizzetti, S.; Benaglia, M.; Raimondi, L.; Celentano, G. (Org. Lett., 2007)

(untitled) - Mlynarski, J.; Bas, S. (Chem. Soc. Rev., 2014)
See for a recent review on organocatalyzed reactions in/on water.

(untitled) - Ilgen, F.; König, B. (Green Chem., 2009)
See for pioneer studies of L-proline in DESs as catalysts of Diels-Alder reactions.

(untitled) - Müller, C. R.; Meiners, I.; Domínguez de María, P. (RSC Adv., 2014)
See for proline-promoted aldol reaction.

(untitled) - Martínez, R.; Berbegal, L.; Guillena, G.; Ramón, D. J. (Green Chem., 2016)

(untitled) - Massolo, E.; Palmieri, S.; Benaglia, M.; Capriati, V.; Perna, F. M. (Green Chem., 2016)
See for primary amine-catalysed transformations in DESs.

(untitled) - Kondo, K.; Yamano, T.; Takemoto, K. (Makromol. Chem., 1985)
See for selected studies on proline immobilization, on polystyrene.

(untitled) - Sakthivel, K.; Notz, W.; Bui, T.; Barbas, C. F., III (J. Am. Chem. Soc., 2001)
See for selected studies on proline immobilization, on silica.

(untitled) - Benaglia, M.; Celentano, G.; Cozzi, F. (Adv. Synth. Catal., 2001)
See for PEG-supported proline.

(untitled) - Calderón, F.; Fernández, R.; Sánchez, F.; Fernández-Mayoralas, A. (Adv. Synth. Catal., 2005)
See for mesoporous silica.

(untitled) - Smith, E. L.; Abbott, A. P.; Ryder, K. S. (Chem. Rev., 2014)

(untitled) - Liu, P.; Hao, J.-W.; Mo, L.-P.; Zhang, Z.-H. (RSC Adv., 2015)

(untitled) - Ruß, C.; König, B. (Green Chem., 2012)

(untitled) - Gu, Y.; Jérôme, F. (Chem. Soc. Rev., 2013)

(untitled) - Francisco, M.; van den Bruinhorst, A.; Kroon, M. C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Alonso, D. A.; Baeza, A.; Chinchilla, R.; Guillena, G.; Pastor, I. M.; Ramón, D. J. (Eur. J. Org. Chem., 2016)

(untitled) - Mallardo, V.; Rizzi, R.; Sassone, F. C.; Mansueto, R.; Perna, F. M.; Salomone, A.; Capriati, V. (Chem. Commun., 2014)

(untitled) - Sassone, F. C.; Perna, F. M.; Salomone, M.; Florio, S.; Capriati, V. (Chem. Commun., 2015)

(untitled) - García-Álvarez, J.; Hevia, E.; Capriati, V. (Eur. J. Org. Chem., 2015)

(untitled) - Cicco, L.; Sblendorio, S.; Mansueto, R.; Perna, F. M.; Salomone, M.; Florio, S.; Capriati, V. (Chem. Sci., 2016)

(untitled) - Mancuso, R.; Maner, A.; Cicco, L.; Perna, F. M.; Capriati, V.; Gabriele, B. (Tetrahedron, 2016)

(untitled) - Capua, M.; Perrone, S.; Perna, F. M.; Vitale, P.; Troisi, L.; Salomone, A.; Capriati, V. (Molecules, 2016)

Use, Health, and Environment - García-Álvarez, J. (Deep Eutectic Solvents and Their Applications as New Green and Biorenewable Reaction Media, 2014)

(untitled) - Hammond, O. S.; Bowron, D. T.; Edler, K. J. (Green Chem., 2016)
See for the first 3D liquid-phase structure of a ChCl-based DES.

(untitled) - Orlandi, M.; Ceotto, M.; Benaglia, M. (Chem. Sci., 2016)

(untitled) - Martínez-Castañeda, A.; Rodríguez-Solla, H.; Concellón, C.; del Amo, V. (J. Org. Chem., 2012)